As várias mortes de um pai: memória e ficção em Miguel Sanches Neto - Hrycyna, Amanda Cristyne (2015)
This paper has the intent to analyze the way the slice of life of the father’s death is reproduced through memory in Miguel Sanches Neto’s autoficcion production. Considering that aim, revisionist bibliography of the author’s texts will be applied, with focus on the novel Chove sobre minha infância (2012) and other short stories, searching for evidences to help us in the comprehension of the importance of the memory in Neto's productions As objectives of the research, can be mentioned an overall look at Miguel Sanches Neto large production when seen from the southern perspective of the dialogue between literature and memory, as well as the investigation of his pieces as an autoficcion based on the theories of Maurice Halbwachs, Michael Pollak, Philippe Lejeune and Serge Doubrovsky. The results show the possibility to study Neto’s works from the memory theory as well as to call his production an autoficction.